The informal sector and gender in the Caribbean : the case of Trinidad & Tobago - Sookram, Sandra (2008)
Seeks to determine the socio-economic and demographic characteristics of individuals engaging in informal sector activity in Trinidad & Tobago. Seeks to ascertain whether there is any wage differential between workers in the formal and informal sectors, and between males and females in the informal sector.